Analisis ECI Dan EPD: Ekspor Bahan Baku Kereta Api dari Jerman, Jepang, dan Australia - Fahrizal Taufiqqurrachman; Ditta Laylia P; Anggita Muawaroh; Dessi Lusianti (Indo Publishing, 2026)
International trade plays a crucial role in driving economic growth and enhancing a country's competitiveness, particularly in strategic industries such as the railway industry, which requires high-tech technology and high-quality raw materials. In the context of globalization and increasingly fierce international market competition, a country's ability to maintain and improve its export performance is a key factor in the industry's sustainability. This study aims to analyze the competitiveness and growth position of railway raw material exports from three key countries—Germany, Japan, and Australia—in the international market. The analytical methods used include the Export Competitiveness Index (ECI) to measure export competitiveness and Export Product Dynamics (EPD) to identify the growth position of export products. The data used are derived from export statistics for specific periods relevant to the development of the global railway industry. The results show that Germany has strong and stable export competitiveness, reflecting its technological superiority and industrial efficiency. Japan exhibits competitiveness that tends to fluctuate but remains at a competitive level, while Australia has considerable export growth potential despite its relatively lower competitiveness compared to the other two countries.